(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
In this current work, we dene and nd the general solution of the tredecic functional equation. We also investigate and establish the generalized Ulam-Hyers stability of this functional equation in matrix normed spaces by using the xed point method.